How Surveillance Motivates New Violence: Ceasefire Monitoring, Remote Sensing Technology, and Noncompliance - Verjee, Aly (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
Monitored ceasefires are thought to be more robust ceasefires, with less noncompliance by conflict parties. Ceasefires monitored with remote sensing technology (RST) such as imaging satellites, uncrewed aerial vehicles, and other camera-equipped assets are widely seen as more effective in deterring conflict party noncompliance. Drawing on insights from surveillance studies, especially from the logics of resistance to surveillance, I argue that the opposite outcome can occur: the use and presence of RST in monitoring may also contribute to new ceasefire noncompliance in the form of new violence. Taking a primarily abductive approach, I theorize how such noncompliance may be produced, identifying four mechanisms. First, the use of RST creates a new class of lower-cost ceasefire violations. Second, the presence of third-party RST incentivizes conflict parties to test the sophistication of monitors’ surveillance. Third, the use of RST by monitors can devalue classical, low-tech monitoring methods. Fourth, the use of RST may inadvertently improve conflict parties’ military abilities. Building on insights from fifty-two interviews and written exchanges with former ceasefire monitors, I demonstrate the presence of these mechanisms in the case of the most technologically advanced ceasefire monitoring mission yet deployed, the Special Monitoring Mission in Ukraine, focusing on the period prior to the Russian invasion of 2022.